Managing enterprise resource planning adoption and business processes a holistic approach - Law, Cheuk-hung Chuck (Cambridge Scholars Publishing, 2019)
The recent decades have witnessed many ERP failures attributable to a plethora of mistakes, and the author writes this book aiming to correct these malpractices concerning ERP adoption. The author presents an adoption methodology, called the Full Lifecycle ERP Adoption Reference (FLEAR) model, to promote holistic project management. Furthermore, from a holistic perspective, successful ERP adoption cannot be achieved in isolation of other business and organizational issues such as IT-business strategic alignment, IT governance, change management, and business process changes. Unlike many ERP boo.